Digital image correlation after focused ion beam micro-slit drilling: A new technique for measuring residual stresses in hardmetal components at local scale. (April 2023) - Dorronsoro, A.; Navarrete, J.; Pan, A.; Castaño, E.; Sánchez, J.M.; Alkorta, J.
Abstract: A new method has been developed for measuring residual stresses at the surface of hardmetal components with higher spatial resolution than standard X-ray diffraction methods. It is based on measuring the surface displacements produced when stresses are partially released by machining a thin slit perpendicularly to the tested surface. Slit machining is carried out by focused ion beam (FIB). Measurement of the displacement fields around the FIB slit are performed by applying an advanced digital image correlation algorithm based on Fourier analysis with sub-pixel resolution. This method compares SEM images of the same area of the hardmetal surface before and after slitting. The method has been successfully applied to as-ground and femto-laser textured surfaces showing good correlation with the standard sin 2 ψ XRD technique. It is concluded that texturing induced by laser pulses in the femtoseconds regime is not perfectly adiabatic, since residual stresses are reduced by 15%. Highlights: Residual stresses were measured on a hard metal subjected to surface laser treatments. Novel FIB-DIC methods were considered for the local measurement of residual stresses. The results were successfully compared with conventional X-Ray diffraction methods. This work confirms that FIB-DIC methods can measure RS at the micrometre scale.